Do Masculine CEOs in High-ESG-Rated Companies Avoid Committing Fraud? Evidence from European Countries - Fritz Karundeng, Frandy Efraim; Szelés, Zsuzsanna (Naše gospodarstvo/Our economy, 2026)
Globally, fraud cases and financial losses remain substantial across European countries. This research offers a novel perspective on the determinants of fraud by examining biological factors, specifically, masculine behavior influenced by the testosterone hormone. CEOs’ masculine tendencies may drive riskier and potentially fraudulent behavior. Notably, masculine traits in males are often reflected in facial structure and can be objectively measured using the facial width-to-height ratio (fWHR). Conversely, robust internal controls and sound corporate governance are critical in preventing fraudulent activities. As global business practices evolve, sustainability has emerged as an urgent concern. In response, companies are increasingly adopting Environmental, Social, and Governance (ESG) principles to promote sustainable operations and mitigate fraud risks. This study investigates whether ESG practices moderate the relationship between CEO masculinity and the likelihood of financial statement fraud. The sample comprises high-ESG-rated firms from 2022 to 2024, as ranked by S&P Global, focusing on publicly listed companies on European stock exchanges. Data were analyzed using the STATA software, employing Fixed Effects Model regression. The results reveal that masculine CEOs in high-ESG-rated companies are less likely to engage in financial misreporting. This finding underscores the importance of balanced ESG implementation in reducing opportunities for misconduct. Furthermore, to enrich future research, the scope of this research could be expanded to include countries in other regions with varying ESG ratings.